Comparative assessment of fracture risk among osteoporosis and osteopenia patients: a cross-sectional study - Tomasevic-Todorovic S (Dove Medical Press, 2018)
Snezana Tomasevic-Todorovic,1 Atina Vazic,2 Abukari Issaka,3 Fahad Hanna4 1Faculty of Medicine, University of Novi Sad, Novi Sad, Serbia; 2Higher School, College of Professional Studies in Education of Teachers, Kikinda, Serbia; 3Department of Climate and Agriculture, School of Science and Health, Western Sydney University, Sydney, NSW, Australia; 4Department of Public Health, College of Health Sciences, Qatar University, Doha, Qatar Background: Both osteoporosis and osteopenia remain worldwide public health concerns. They both lead to bone fractures, which can lead to disability and burden on those who are afflicted.Objectives: To assess and compare fracture risk between these two groups of patients.Patients and methods: Our cross-sectional study included 82 patients (46 with osteoporosis and 36 with osteopenia) with an average age of 63±9.33 years, who received treatment at the Clinic for Medical Rehabilitation, Clinical Center of Vojvodina in Novi Sad, Serbia. The assessment of the fracture risk was executed by applying the Fracture Assessment Risk (FRAX) index (an algorithm developed by the World Health Organization) based on clinical fracture risks or combination of clinical fracture risks and bone mineral density.Results: Patients with osteoporosis had significantly higher risk of major fracture compared to patients with osteopenia (p<0.01). Results from FRAX index in osteoporotic patients showed that more than half (58.70%) of patients had a low risk of fracture; less than one-third of patients (30.43%) had an intermediate risk of major osteoporotic fracture, while almost four out of every 10 (39.96%) had a high risk of hip fracture. The majority of patients with osteopenia (63.89%) had a low risk of major osteoporotic fracture, while 36.11% of them had an intermediate risk. The majority of patients with osteopenia (91.67%) had a low risk of hip fracture. Statistically significant differences in relation to specific fracture risks between patients with osteoporosis and osteopenia, in particular, weight (t=−2.250, p=0.027*) and previous fractures (t=2.985, p=0.004**), were established.Conclusion: Osteoporosis patients had a high risk of major osteoporotic fracture, while there was no association between the intermediate level for major osteoporotic fracture and osteopenia. For patients suffering from an increased fracture risk, especially those who had already been diagnosed with osteoporosis, preventive measures such as designing individual therapeutic programs should be adopted. Keywords: osteoporosis, osteopenia, fracture risk, fractures, FRAX index, bone fracture, body mass index, bone mineral density